The impact of Economics and Finance research published in Central and Eastern Europe - Krueger, Thomas M.; Megits, Nikolay (Journal of Eastern European and Central Asian Research (JEECAR), 2021)
Research quality dictates the reputation of faculty, colleges, and universities, regardless of their location. In order to shed some light on the quality construct, this research reports on the scholarly impact of economics and finance journals published in countries of Central and Eastern Europe. A comparison of coverage by Web of Science (WoS), Scopus, and Cabell’s, three scholarly databases, reveals the lesser coverage of CEE journals within WoS and Scopus. Examination of E&F journals published in Poland, Romania, and the remainder of CEE, as defined by the Journal of Eastern European and Central Asian Research, discloses that the level of quality varies by nation. There are variations across the popular CiteScore, SJR, SNIP, and percentage of articles cited bibliometric measures. Furthermore, this research documents the existence of impact variation between journals focused on Eastern Europe published in Eastern Europe and published elsewhere in the world.